Pengaruh Brand Image, Harga, dan Fashion Lifestyle terhadap Keputusan Pembelian Pakaian Preloved di Thriftshop dalam Perspektif Bisnis Syariah: (Studi kasus Konsumen Diviwearstore) - Melinda Septri Yani; Evi Ekawati; Weny Rosilawati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The fashion industry is a dynamic and globally influential economic sector. As part of culture and personal expression, fashion not only meets the need for clothing but also reflects identity, social values, and societal aesthetic trends. A current trend is branded preloved fashion, often referred to as thrifting. This quantitative study uses primary data, with a sample of 86 consumers from Diviwearstore, using a purposive sampling method. Collected through questionnaires using a Likert scale. Data analysis is conducted using SPSS(Statistical package for the social Science) version 20.